Septal myectomy in the era of genetic testing. Issue 4 (5th February 2021) - Chauvette, Vincent; Accad, Albert J.; Georges, Gabriel; Bouhout, Ismail; Garceau, Patrick; L'Allier, Philippe; Bouchard, Denis
Abstract: Background: Hypertrophic obstructive cardiomyopathy (HOCM) is one of the most common genetic cardiac diseases and encompasses an array of clinical presentations. Little is known about the impact of genetic background on outcomes after septal myectomy (SM). The aim of this study was to evaluate the effect of specific genetic mutations on midterm outcomes in adults undergoing SM for HOCM. Methods: From 2003 to 2020, a total of 59 patients (male = 66%, mean age = 52 ± 13) underwent SM after a preoperative genetic test. Patients were divided into two groups according to their test result (positive or negative). Preoperative echocardiograms were examined to identify phenotypical characteristics of each mutation. Results: A total of thirty‐one patients (53%) had a positive genetic test. MYBPC3 was the most common mutation (15/31 patients). Four different phenotypes were identified on preoperative echocardiograms. Overall, Type 1 phenotype was the most common (37% of the cohort). Type 3 was found exclusively in patients with a positive genetic test. Following SM, none of the patients required a redo myectomy or septal ablation. At 10 years, the survival was 97 ± 3% and 100% in patients with a positive and negative genetic test ( p  = .33), respectively. Conclusion: Although our results suggest that the multiple gene mutations present with different characteristics and phenotypes, midterm results of SM appear to be good regardless of genetic mutation presence.